A strategic Vision to Reduce Cyber-crime and Enhance Cyber security - Ahmed Alkaabi, (International Journal of Advanced Science and Technology, 2020)
The number of internet users has gradually increased over the last two decades majorly due to therelevance of online services in people’s daily lives. With increased internet use, more dynamic technologieshave emerged which has potentially increased the threats or risks associated with online services. Thisstudy focused establishing strategies to help prevent cybercrimes and enhance cybersecurity. It is clearthat most cyber-attacks arise due to human error which is associated with lack of knowledge about differentdynamics of cybercrimes and cyber security. In this case, increasing knowledge of IT personnel and otherrelevant staff about the dynamics of cybersecurity is very essential in reducing cybercrime and enhancingcyber security. It is also recommended that governments should focus on establishing cybersecurityframeworks and laws or legislations to help in addressing cybercrimes.